Respuesta :

Answer: (-1,4)

Step-by-step explanation:

y=-2x+2                                    y=7x+11 <----- substitute this equation for y in the            

                                                                       equation y=-2x+2

7x+11=-2x+2              Add 2x to both sides

9x+11=2                     Subtract 11 from both sides

9x=-9                         Divide both sides by 9

x=-1

y=-2(-1)+2                   Plug in x to one of the equations, I chose y=-2x+2            

y=2+2                         because it was the easiest, then solve

y=4

Solution is (-1,4)